Insights into peptide‐membrane interactions of newly synthesized, nitroxide‐containing analogs of the peptaibiotic trichogin GA IV using EPR. Issue 1 (29th January 2017) - Bortolus, Marco; Dalzini, Annalisa; Maniero, Anna Lisa; Panighel, Giacomo; Siano, Alvaro; Toniolo, Claudio; De Zotti, Marta; Formaggio, Fernando
Abstract: Trichogin GA IV is a short‐length (10‐amino acid long), mostly hydrophobic, peptaibiotic with an N‐terminal fatty acyl chain and a C‐terminal 1, 2‐amino alcohol. A cardinal role of the terminal moieties in the cytotoxic activity of trichogin has been recently found. Previously, peptide orientation and dynamics of trichogin analogs in the membrane were studied using methyl ester derivatives. Therefore, in the present work we synthesized several trichogin analogs with naturally occurring terminal groups to verify whether these moieties have any effect on peptide‐membrane interaction. These trichogin analogs, both neutral and carrying a positively charged Lys residue, bear the nitroxide‐containing α‐amino acid TOAC to study them using EPR spectroscopy. Vesicles were used to investigate orientation and penetration depth of the peptide at room temperature. Bicelles were employed to evaluate the order, dynamics, and orientation of the peptide at a near physiological temperature. In addition, the position of the N‐terminal 1‐octanoyl chain in the membrane was studied by labeling it with a nitroxide. The secondary structure of the peptides in vesicles was studied by CD spectroscopy showing that they adopt a mostly α‐helical structure. In vesicles, the analogs insert below the lipid headgroups with the helix axis oriented parallel to the membrane surface at a peptide‐to‐lipid ( P : L ) ratio of 1:100. The presence of the single, positively charged Lys residue does not alter the orientation adopted by the peptides. In bicelles at P : L ratios 1:100 and 1:60, the peptide adopts a transmembrane orientation characterized by a very low orientational order, whereas at a 1:15 P : L ratio it severely disrupts the membrane. Our data shows that overall orientation and insertion in model membranes of the native trichogin GA IV are strictly comparable to those of its methyl ester analogs previously examined.